KUZNET’S HYPOTHESIS AND IBN KHALDUN’S SOCIO-ECONOMIC DIMENSIONS - Indriati, Isnan; Nugroho, Muh Rudi (Shirkah: Journal of Economics and Business, 2019)
This study aims to prove the relationship between the hypothesis of Kuznets and Ibn Khaldun's socio economic dimension and income inequality. The object employed in this study is five municipal districts in Yogyakarta with the highest value of inequality throughout Java. This research utilizes the data panel which is a combination of annual time series of data from 2004-2017 and cross section of data from the five municipal districts in Yogyakarta. In this study, dynamic data panel regression is performed with the Generalized Method Moment (GMM) Arellano Bond. The relationship of the economic dimension of Ibn Khaldun and income inequality has been used to calculate income inequality Theil Entropy index which is being the dependent variable, and other variables as proxy for each dimension in Ibn Khaldun's socio-economic dimension models. The result of this study indicates that the linkage between Kuznets's hypothesis and Ibn Khaldun's socio-economic dimensions is similar since the economic growth shows insignificant variable resulted in both models. Keywords: Kuznets hypothesis, Ibn Khaldun's socio-economic dimensions, Entropy Theil Index, Generalized Moment Method (GMM) Arellano Bond.